Formação de diretores em Centro de Educação Infantil Conveniado: um estudo exploratório - Brustolin, Renata Martins dos Santos (2018)
This study aimed to analyse the principal training needs who act in Child Education Centre, from the affiliated network, situated in the south region of São Paulo, including the neighbourhood which compose the districts of Campo Limpo, Vila Andrade, Capão Redondo, Jardim Ângela and Jardim São Luís, and which are part of a territory served by the Education Regional Directory of Campo Limpo. This study was carried out from May to June of 2018. The research is developed in a perspective of a qualitative approach based in the studies of Lüdke and André (1986). The methodological procedure used in the data production was a questionnaire applying, edited in the Google forms, which had classification, open and attitudes scale questions. The information analysis process was done from the answer categorization organized by the proximity of sense and meanings building semantic sets and, later, by textual analysis called “Words Cloud”, using the software Iramuteg which organized the expressions that appeared more often. This procedure allowed a lexical analysis with the aim to validate the primary interpretation of this beginner researcher. From the analysis it was observed that continuing education investment is needed for the principals who act in these institutions, in order to better understand the public policies of care for children from zero to three years old and to develop a high-quality work